Case report: Symmetrical and increased lateral sway-based walking training for patients with corpus callosum infarction: a case series - Jiang, Ying; Chen, Sijing; Wu, Dan; He, Wei; Ma, Xiaoqing; Zhang, Lixia; Zhang, Qian (Frontiers in Neurology, 2024)
Introduction: Corpus callosum injury is a rare type of injury after stroke that can cause lower limb dysfunction and a decrease in daily living ability. Furthermore, there are no studies that focus on the rehabilitation progress of lower limb dysfunction caused by infarction in the corpus callosum and the effective treatment plans for this condition. We aimed to present a report of two patients with lower limb dysfunction caused by corpus callosum infarction after stroke and a walking training method. Methods: We implemented a walking training method that prioritizes bilateral symmetry and increases lateral swaying before the patients established sitting/standing balance. The plan is a rapid and effective method for improving walking dysfunction caused by corpus callosum infarction. Case characteristics: Following sudden corpus callosum infarction, both patients experienced a significant reduction in lower limb motor function scores and exhibited evident gait disorders. Scale evaluations confirmed that walking training based on symmetrical and increased lateral sway for patients with lower limb motor dysfunction after corpus callosum infarction led to significant symptom improvement. Conclusion: We report two cases of sudden motor dysfunction in patients with corpus callosum infarction. Symmetrical and increased lateral sway-based walking training resulted in substantial symptom improvement, as confirmed by scale assessments.